Question
upstudy study bank question image url

7 VOU \& MATHS Consider the following functions: \[ f(x)=2 x-4, g(x)=2 x+4 \text {, } \] \[ h(x)=9 x+3 \text {. } \] Are there inputs that give the same outputs for functions \( f \) and \( g \) ? And for functions \( f \) and \( h \) ? And for \( g \) and \( h \) ?

Ask by Sherman Brewer. in Italy
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Non ci sono input che danno lo stesso output per le funzioni \( f \) e \( g \). Le funzioni \( f \) e \( h \) danno lo stesso output per \( x = -1 \). Le funzioni \( g \) e \( h \) danno lo stesso output per \( x = \frac{1}{7} \).

Solution

Per determinare se ci sono input che danno gli stessi output per le funzioni \( f \), \( g \) e \( h \), dobbiamo risolvere i seguenti sistemi di equazioni: 1. \( f(x) = g(x) \) 2. \( f(x) = h(x) \) 3. \( g(x) = h(x) \) Iniziamo a risolvere ciascuna di queste equazioni. ### 1. Risolvere \( f(x) = g(x) \) \[ 2x - 4 = 2x + 4 \] Semplificando l'equazione: \[ -4 = 4 \] Questa equazione non ha soluzioni, quindi non ci sono input che danno lo stesso output per le funzioni \( f \) e \( g \). ### 2. Risolvere \( f(x) = h(x) \) \[ 2x - 4 = 9x + 3 \] Semplificando l'equazione: \[ 2x - 9x = 3 + 4 \] \[ -7x = 7 \] \[ x = -1 \] Quindi, per \( x = -1 \), le funzioni \( f \) e \( h \) danno lo stesso output. ### 3. Risolvere \( g(x) = h(x) \) \[ 2x + 4 = 9x + 3 \] Semplificando l'equazione: \[ 2x - 9x = 3 - 4 \] \[ -7x = -1 \] \[ x = \frac{1}{7} \] Quindi, per \( x = \frac{1}{7} \), le funzioni \( g \) e \( h \) danno lo stesso output. ### Risultato finale - Non ci sono input che danno lo stesso output per le funzioni \( f \) e \( g \). - Le funzioni \( f \) e \( h \) danno lo stesso output per \( x = -1 \). - Le funzioni \( g \) e \( h \) danno lo stesso output per \( x = \frac{1}{7} \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find the inputs that give the same outputs for the functions \( f(x) \), \( g(x) \), and \( h(x) \), we need to set them equal to each other and solve for \( x \). 1. For \( f(x) \) and \( g(x) \): \[ 2x - 4 = 2x + 4 \] Simplifying this gives \( -4 = 4 \), which is a contradiction. So, there are no inputs that provide the same output for \( f(x) \) and \( g(x) \). 2. For \( f(x) \) and \( h(x) \): \[ 2x - 4 = 9x + 3 \] Rearranging gives us \( -4 - 3 = 9x - 2x \) leading to \( -7 = 7x \) or \( x = -1 \). Thus, \( f(-1) = h(-1) = -6 \). 3. For \( g(x) \) and \( h(x) \): \[ 2x + 4 = 9x + 3 \] Rearranging gives us \( 4 - 3 = 9x - 2x \) leading to \( 1 = 7x \) or \( x = \frac{1}{7} \). Thus, \( g\left(\frac{1}{7}\right) = h\left(\frac{1}{7}\right) = \frac{18}{7} \). In summary: - No inputs yield the same outputs for \( f \) and \( g \). - The input \( x = -1 \) gives the same output for \( f \) and \( h \). - The input \( x = \frac{1}{7} \) gives the same output for \( g \) and \( h \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy